Homelessness youth and mental health service utilization: A long‐term follow‐up study. Issue 3 (19th May 2020) - Russell, Melissa; Soong, Wei; Nicholls, Craig; Griffiths, Jennifer; Curtis, Kerry; Follett, Denise; Smith, Warwick; Waters, Flavie
Abstract: Background: There is currently an incomplete picture of the long‐term impact of homelessness on youth with mental health issues. There are also questions regarding homelessness as a predictor of mental health re‐admissions. Aims: To examine the mental health service presentation profile of young people affected by homelessness and mental health issues. Methods: A retrospective analysis was conducted of the medical records of homeless (n = 29) and non‐homeless (n = 32) youth who attended the YouthLink specialist mental health service in 2010. We tracked their pattern of mental health service admissions at five time points during a total period of 10 years, including 2 years prior to, and up to 8 years following the YouthLink presentation. A regression analysis was used to examine factors hypothesized to contribute to mental health re‐admissions. Results: Homeless youth had significantly more frequent presentations to inpatient and outpatient mental health services, and emergency departments for mental health reasons. They were 11 times more likely to be re‐admitted to a mental health inpatient ward than non‐homeless youth. Prior hospital admission was an independent predictor, increasing by a factor of 2.2 for every inpatient admission. Conclusion: The impact of homelessness on mental health issues is enduring, and is a long‐term predictor of hospital re‐admission.